Effects of agricultural subsidies on farm household decisions: a separable household model approach - Lal, Priyanka; Chandel, B. S.; Tiwari, Rahul Kumar; El-Sheikh, Mohamed A.; Mansoor, Sheikh; Kumar, Alok; Singh, Gyanendra; Lal, Milan Kumar; Kumar, Ravinder (Frontiers in Sustainable Food Systems, 2023)
This study employs a separable household model to estimate the effect of agricultural subsidies on production and consumption decisions taken by farm households. The study used data from a household survey using a pre-tested schedule to develop and calibrate an agricultural household model. First, we calculated a price index for the model. The index was higher for non-agricultural commodity groups in all the categories of farm households. Expenditure on non-agricultural commodity groups was more than agricultural commodity groups. Results indicated that for the agricultural commodity group, the estimated coefficients of Linear Expenditure System (LES) model were positive and less than one for all farm household categories except for the wage-price coefficient which was found to be negative. The estimates of profit function in the study area depict that the variable inputs were negatively related to the profit function and the fixed inputs were positively related to profit. Our study highlights a few crucial points -First, the removal of subsidies will decrease the demand for electricity, concentrate and irrigation by 80, 73 and 70 %, respectively. Second, removing subsidies will not only affect the demand for inputs but will also lead to a decline in the consumption demand for both agricultural and non-agricultural commodities. Third, this effect was found to be more prominent in the small and medium categories of farm households.